Confirmation of hard-substrate predictions in the abyssal Vema Fracture Zone - Riehl, Torben; Budke, Linus; Brandt, Angelika; Henseler, Mats; Martínez Arbizu, Pedro; Momtazi, Farzaneh; Augustin, Nico (Frontiers in Marine Science, 2025)
Hydroacoustic mapping has recently challenged the long-held view of a uniform abyssal seafloor by predicting substantial habitat heterogeneity in this environment. The RUBBLE expedition M205 validated these predictions in the Vema Fracture Zone (VFZ) with visual surveys at six locations using a towed deep-sea camera system. Exposed rock outcrops and varied hard substrates were consistently confirmed in areas of high hard-rock exposure, while moderately predicted areas contained a mix of sediments, cobbles, and pebbles; low-potential sites were almost entirely covered in sediment. Although a detailed quantification is beyond the scope of this report, visual correspondence supports the reliability of hydroacoustic predictions for abyssal habitats. Notably, this study pioneers the application of hydroacoustic-based seafloor characterization at abyssal depths—extending methods formerly focused on bathyal zones to the planet’s largest benthic environment and enabling direct ground-truthing of habitat models below 5,000 m. These findings highlight abyssal habitat heterogeneity, confirm the utility of hydroacoustic tools for broad-scale benthic mapping, and establish a baseline for future research on deep-sea biodiversity and ecological dynamics.